2017
DOI: 10.1111/aas.12903
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia after nontraumatic intracranial hemorrhage

Abstract: Hypophosphatemia was common in this patient population. The outcome was similar between hypophosphatemic and normophosphatemic patients. Chronic hypertension, acute hydrocephalus, diffuse brain edema and higher SOFA scores were more common in patients with hypophosphatemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 30 publications
(44 reference statements)
7
29
2
Order By: Relevance
“…Given that hypophosphatemia was variably defined among studies, sensitivity analysis was subsequently performed on different hypophosphatemia thresholds defined by the authors. Studies that performed their analysis based on a definition of serum phosphate level ≤0.80 mmol/L 15,16,30 –32,34 36 showed some evidence for a higher risk of mortality in the group of patients with hypophosphatemia compared to those without (RR, 1.27 [95% CI, 1.00-1.60]; P = .048; Table 2). The remainder 4 studies that performed their analyses with serum phosphate level of >0.80 mmol/L 28 30,33 did not demonstrate a statistically significant result (RR, 0.97 [95% CI, 0.78-1.21]; P = .81; Online Appendix E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Given that hypophosphatemia was variably defined among studies, sensitivity analysis was subsequently performed on different hypophosphatemia thresholds defined by the authors. Studies that performed their analysis based on a definition of serum phosphate level ≤0.80 mmol/L 15,16,30 –32,34 36 showed some evidence for a higher risk of mortality in the group of patients with hypophosphatemia compared to those without (RR, 1.27 [95% CI, 1.00-1.60]; P = .048; Table 2). The remainder 4 studies that performed their analyses with serum phosphate level of >0.80 mmol/L 28 30,33 did not demonstrate a statistically significant result (RR, 0.97 [95% CI, 0.78-1.21]; P = .81; Online Appendix E and F).…”
Section: Resultsmentioning
confidence: 99%
“…although not in all [26,27,[41][42][43][44]. In contrast, hypophosphatemia secondary to CRRT has limited clinical consequences in most retrospective studies [19,[45][46][47][48] (possibly related to "preventive" phosphate administration [49]), but not in all [34,48,50].…”
Section: Q1+2: Is Hypophosphatemia Associated With Development Of Organ Failures and Impaired Outcome In Adult Icu Patients?mentioning
confidence: 99%
“…The model constructed by sPi levels, Hunt-Hess grade, and mFisher scale produced the best ability to predict aHCP compared with a single sPi level or mFisher scale, which was a valuable factor for predicting the occurrence of aHCP following aSAH. Previously reported literature demonstrated that aHCP and diffuse cerebral edema are more common in patients with non-traumatic intracranial hemorrhage accompanied by decreased sPi levels [17]. Based on it, we listed aSAH from non-traumatic ICH to explore the relationship between decrease sPi levels and aHCP.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, impressive literature reported that hypophosphatemia is associated with a disturbance of consciousness after spontaneous intracerebral hemorrhage (sICH), but its mechanism is still poorly understood [19]. Emerging literature indicated that hypophosphatemia is associated with HCP after sICH in the ICU [17]. However, the patients enrolled in this study were mixed with other causes of intracerebral hemorrhage, and the number of patients with ICH was small, so there was a particular research bias.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation